1978
DOI: 10.1139/f78-215
|View full text |Cite
|
Sign up to set email alerts
|

Capture Probability: The Role of Zooplankter Escape in the Selective Feeding of Planktivorous Fish

Abstract: The conditional probabilities (P3) of being captured by a simulated fish-suction intake ranged from P = 0.76 to P = 0.96 for cladocerans and from P = 0.07 to P = 0.28 for copepods. Gizzard shad (Dorosoma cepedianum) feeding experiments confirmed that these differential capture probabilities can result in an apparent planktivore feeding selectivity for cladoceran zooplankters. Key words: capture probability, zooplankter escape, planktivore feeding selectivity, gizzard shad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
195
0
5

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(208 citation statements)
references
References 0 publications
8
195
0
5
Order By: Relevance
“…In particular, because cyclopoids can alter their swimming speeds (Drenner et al 1978), they may be better able than cladocerans to escape the suction force created by the opening of the relatively narrow trapdoor of U. gibba. In addition, for U. sp.2, we observed more and less colonization by epibionts.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, because cyclopoids can alter their swimming speeds (Drenner et al 1978), they may be better able than cladocerans to escape the suction force created by the opening of the relatively narrow trapdoor of U. gibba. In addition, for U. sp.2, we observed more and less colonization by epibionts.…”
Section: Discussionmentioning
confidence: 99%
“…Gizzard shad from 8-to 20-cm SL were electrofished from Lone Star Lake, Douglas County, Kansas, and stocked into two of the quadrants at densities of 233 and 257 kgaha-' on 25 June 1978 (see Drenner et al 1982a). Phytoplankton samples were collected with a column sampler (deNoyelles and O'Brien 1978).…”
Section: Methodsmentioning
confidence: 99%
“…Treatment effects from 29 June to the end of the experiment were analyzed with a splitplot analysis of variance (ANOVA for repeated measures) (Winer 197 1;Gill 1978). Because the original analysis of shad effects on zooplankton (Drenner et al 1982a) was statistically invalid, we also reanalyzed the zooplankton data with a split-plot ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…This is in contrast with the finding of Chang & Hanazato (2003) and Lapesa et al (2002). For C/A, it is clear that ability to swim faster, especially during escape situations, may be directly correlated to body size (Drenner et al 1978, Drenner & McComas 1980. It is also clear that mechanical disturbances produced by faster and larger bodies may be stronger, thereby allowing prey to be detected more precisely for mechanoreceptors of cyclopoid copepods (Williamson 1986).…”
Section: Discussionmentioning
confidence: 85%
“…While Diaphanosoma exhibit a rapid powerful stroke of their second antennae allowing escape from attack volume of the predator, Ceriodaphnia species increase swimming speed as an escape response, although they tend to stay inside of volume attack of the predator. Recently Chang & Hanazato (2003) have indicated that swimming behavior of single strokes in Diaphanosoma may be effective at avoiding fish predation (Drenner et al 1978, Drenner & McComas, 1980, but fail as a defense mechanism against some copepod species. Contrarily, our observations show that efficiency of this defense mechanism against attacks of T. decipiens is highly effective.…”
Section: Discussionmentioning
confidence: 99%